The International Monetary Fund interventions in Greece post the 2008 global economic crises - Dakile, Dumisani Andrias (My University, 2018)
The 2008 global economic crises which originated in the United States of America had a devastating effect to the international community. The International Monetary Fund played a significant role as the Global Development Finance Institutions during the 2008 global economic crises. The purpose of this research is to understand how the IMF intervened in Greece because of the 2008 global economic crises and how such interventions affected the working class and the poor. The researcher adopted a qualitative research methodology, undertook interviews and used questionnaires to experts, academics, trade unionist, embassy representative knowledgeable on the 2008 economic crises and the IMF role in the Greece crises. The researcher also reviewed various documents and reports as a further resource to comprehend, gain more sight and to obtain pertinent and appropriate data on the subject matter. The researcher utilized uniform questions for all the participants across. The research has established the role that was played by the IMF in the Greece crises which has been very controversial, why Greece it continues to be in economic crises and what should be done differently to resolve the Greece crises. It has established how the working class and the poor had been affected the IMF intervention in Greece and lastly it has proposed measures which need to be undertaken by the Greece to resolve the crises.
A research report submitted to the Faculty of Commerce, Law and Management of the University of Witwatersrand, Johannesburg in part of the requirements for the Degree in Management in Public and Development. April 2018
Keywords: International Monetary Fund; Global Financial Crisis, 2008-2009; Financial crises